THE EFFECTIVENESS OF USING STORY MAP TECHNIQUE TOWARDS STUDENTS READING COMPREHENSION ON NARRATIVE TEXT (A QUASI EXPERIMENTAL STUDY) - Rika Nurhikmah Sugandi; Yudi Juniardi; Eri Rahmawati (Undiksha Press, 2022)
The aim of this research is to find out the effectiveness of using story map technique towards students reading comprehension on narrative text. The methodology used in this study was quantitative method. The design of this study was quasi experimental design. The population of this research was the tenth grade students of SMKN 01 Kragilan. The sample of this research was chosen based on the random sampling technique. The class was put into the experimental class and control class, each class consisted of 20 students. Pre-test was given to both classes at the beginning phase. Then treatment was given only to the experimental class. To find the effectiveness, post-test was given to the class. The data was collected through pretest and posttest that analyzed by using t-test formula. The result of the research showed that story map as a technique is effective towards students reading comprehension in narrative text. The calculation result of t-test showed that Tcount ≥ Ttable, 5.85 ≥ 2.00, it can be said that Alternative Hypothesis (Ha) was accepted and the Null Hypothesis (H0) was rejected, it means that the use of story map technique was considered effective in teaching reading comprehension on narrative text.